2009
DOI: 10.1063/1.3238508
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of electrical properties and deep traps in p-AlxGa1−xN grown by molecular beam epitaxy and metal organic chemical vapor deposition

Abstract: The electrical properties, admittance spectra, microcathodoluminescence, and deep trap spectra of p-AlGaN films with an Al mole fraction up to 45% grown by both metal organic chemical vapor deposition (MOCVD) and molecular beam epitaxy (MBE) were compared. The ionization energy of Mg increases from 0.15 to 0.17 eV in p-GaN to 0.3 eV in 45% Al p-AlGaN. In p-GaN films grown by MBE and MOCVD and in MOCVD grown p-AlGaN, we observed additional acceptors with a concentration an order lower than that of Mg acceptors,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
18
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 20 publications
2
18
0
Order By: Relevance
“…In most cases the activation energies for both peaks are close to each other and to the Mg ionization energy determined from Hall/van der Pauw measurements, but the pre-exponential factor for the low temperature peak yields the apparent hole capture cross section of 10 À16 to 10 À15 cm 2 , while the high temperature peak is characterized by a very much lower apparent hole capture cross section of 10 À20 to 10 À19 cm 2 [115][116][117][118]. It has been reported that the magnitude of the capacitance step and the admittance peak related to the low temperature feature is greatly increased by hydrogen plasma treatment (and proton irradiation) of p-GaN:Mg samples [115,116]. The relative magnitude of the low temperature step was also found to be lower in MBE growth or HVPE growth in Ar atmosphere as opposed to MOCVD growth [115] (in both cases the hydrogen concentration is very considerably lower than the Mg concentration, see e.g.…”
Section: Mg In Iii-nitridessupporting
confidence: 61%
See 4 more Smart Citations
“…In most cases the activation energies for both peaks are close to each other and to the Mg ionization energy determined from Hall/van der Pauw measurements, but the pre-exponential factor for the low temperature peak yields the apparent hole capture cross section of 10 À16 to 10 À15 cm 2 , while the high temperature peak is characterized by a very much lower apparent hole capture cross section of 10 À20 to 10 À19 cm 2 [115][116][117][118]. It has been reported that the magnitude of the capacitance step and the admittance peak related to the low temperature feature is greatly increased by hydrogen plasma treatment (and proton irradiation) of p-GaN:Mg samples [115,116]. The relative magnitude of the low temperature step was also found to be lower in MBE growth or HVPE growth in Ar atmosphere as opposed to MOCVD growth [115] (in both cases the hydrogen concentration is very considerably lower than the Mg concentration, see e.g.…”
Section: Mg In Iii-nitridessupporting
confidence: 61%
“…In the second case, the activation energy is that of the temperature dependence of conductivity [111]. In many cases experimentally measured admittance spectra show two distinct peaks in admittance/steps in capacitance [112][113][114][115][116]. This is illustrated by Fig.…”
Section: Mg In Iii-nitridesmentioning
confidence: 97%
See 3 more Smart Citations